CSR in Business for Sustainable Enterprise (Don Bosco Institute of Technology Delhi Journal of Research, 2024)
Over time, businesses have added additional components, such corporate  governance, service-dominant thinking, and sustainable business. Examples of  these include corporate social responsibility. It used to be said that an organization’s  main responsibility was to maximize profits for its stakeholders at the expense of its  ability to improve society as a whole. Ecology, another important component that  was previously disregarded, is now receiving the attention it deserves. A “business  case” for corporate sustainability is a concept that more and more businesses,  environmental groups, and others are adopting to bolster their sustainable business  practises. No company can stay in business for very long if it withdraws from  these operations. Therefore, it is now essential to engage in responsible corporate  citizenship in the contemporary economic environment by  Understanding these phrases and integrating them into company social culture is  increasingly essential. The theoretical examination of corporate social responsibility  (CSR) in this article will primarily center on the triple bottom line (TBL) in terms  of the economic, social, and environmental components. The study of corporate  social responsibility (CSR) for sustainable business will be built around the triple  bottom line, with a focus on the importance of this concept for running sustainable  businesses. The value that companies may provide to their clientele will determine  how corporate businesses turn out.
Keywords: Triplebottomline; philanthropy; stakeholders; ethics